Identification of Peat Soil Thickness Using the 2D Electrical Resistivity Method: Case Study Bansir Darat Subdistrict, Pontianak City - Dwi Ishika Noviandita; Zulfian Zulfian; Joko Sampurno (Departement of Physics Faculty of Mathematics and Natural Sciences, and Institute of Research and Community Services Udayana University, Kampus Bukit Jimbaran Badung Bali, 2026)
Bansir Darat is a sub-district that utilizes peatland for residential areas. Therefore, information about peatland thickness is essential for the community in the sub-district. This study aims to identify the thickness of peatland in the Bansir Darat sub-district. The geoelectric resistivity method using the Wenner-Schlumberger configuration was used in this measurement. Data collection was carried out on three tracks with a length of 50 m each and the smallest electrode spacing of 2 m. The obtained field data were inverted using the Least Squares Inversion method. The inversion results in the form of a resistivity cross-section with peatland soil estimated to have a resistivity value of 0.687 - 24.2 Ωm. The interpretation results indicate that the thickness of the peatland varies between 1.5 - 6 m. Information regarding the thickness of the peatland can be used in planning residential development by the local community.